PENGELOLAAN AKREDITASI SEKOLAH MENENGAH ATAS OLEH BADAN AKREDITASI PROVINSI BENGKULU - Edi Efendi; Aliman Aliman (UNIVERSITAS BENGKULU, 2020)
This qualitative study described in depth and comprehensive management of quality improvement of personnel performance in the field of manpower development in the Office of Education and Culture of Bengkulu Province. The subjects were principals, vice principals, and employees of school aministrasion. Data collection techniques used interview, observation and documentation. Data were analyzed using qualitative analysis technique. The results to ensure that every high schools in Bengkulu both state and private are managed based on national standards of education.